2016
DOI: 10.1590/1806-9061-2015-0065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Stress on the Expression of GABA Receptor mRNA in the HPG Axis of Wenchang Chickens

Abstract: We investigated the effect of heat stress (HS) on the expression of the GABA receptor in the hypothalamic-pituitary-gonadal (HPG) axis of Wenchang chickens. Real-time quantitative RT-PCR (qRT-PCR) was used to quantify the GABA receptor mRNA levels along the HPG axis of chickens under HS (40±0.5 °C) for 1-6 weeks. Our results showed that the expression of GABA A and GABA B receptor at the mRNAs levels in the tissues of HPG axis exhibited fluctuation and variability. After HS, the mRNA level of GABA A receptor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…A characteristic of broiler chickens reared under high temperature stress is a rapid decline of weight gain after the early period. According to multiple reports on the rearing of broiler chickens and turkeys, body weight, feed intake, and feed conversion ratio decreased in high temperature environments compared to a general environment [ 18 , 19 ], and the present study also confirmed these phenomena. The present study identified the effects of the addition of a single supplement, GABA (GB50, GB150).…”
Section: Discussionsupporting
confidence: 87%
“…A characteristic of broiler chickens reared under high temperature stress is a rapid decline of weight gain after the early period. According to multiple reports on the rearing of broiler chickens and turkeys, body weight, feed intake, and feed conversion ratio decreased in high temperature environments compared to a general environment [ 18 , 19 ], and the present study also confirmed these phenomena. The present study identified the effects of the addition of a single supplement, GABA (GB50, GB150).…”
Section: Discussionsupporting
confidence: 87%
“…However, the mRNA expression of Gad1 was significantly reduced in fish supplied with GABA in the diet which might ultimately balance the GABA levels in the CNS of juvenile olive flounder at the high water temperature and relieve the temperature stress. Likewise, Xie et al [ 46 ] reported the positive effects of supplemental GABA in terms of increased mRNA expression of GABAergic receptors such as GABA A and GABA B in the hypothalamic–pituitary–gonadal (HPG) axis of Wenchang chickens. However, these researchers also reported that the GABA A and GABA B receptors showed fluctuations at mRNA levels and variability in the tissues of the HPG over 1–6 weeks of heat stress in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional compounds like GABA (a non-protein amino acid) functions as neurotransmitter inhibitor and exhibit hypotensivity [7]. GABA is one of the most important functional components in fermented foods due to its physiological functions such as neurotransmission and antihypertensive activities [8], and anti-heat stress for broilers [9]. Nonetheless not much is known about GABA-rich fermented foods that can be used as feed additives.…”
Section: Introductionmentioning
confidence: 99%